Firms Going Global, Communication Going Sensitive. Cultural Sensitivity: A Challenge for Global Companies in Saudi Arabia - Saliba, Stephanie; Salem, Ghada (British Journal of Marketing Studies, 2024)
This research examines the intricacies of cultural sensitivity throughout global advertising efforts, specifically with regard to Saudi Arabia. Employing interpretation as the philosophical framework and a mixed-methods technique, this study investigates the perceptions and attitudes of Saudi residents towards culturally sensitive advertising. The findings indicate a notable inclination among Saudi individuals towards commercials that are in line with their cultural values, emphasizing the significance of language, traditions, and religious observance. Expert interviews highlight the difficulties and advantages linked to worldwide advertising standardization, highlighting the importance of being culturally sensitive. Secondary data analysis confirms the importance of respecting local cultural norms, as evidenced by society responses and manifestations. In addition, the study examines the concept of glocalization in advertising, emphasizing the significance of adapting global marketing strategies to suit specific local contexts. This study offers practical knowledge for global companies seeking to handle cultural sensitivity in the Saudi market. It highlights the significance of aligning advertising strategies with local cultural norms to improve customer engagement and brand perception